The over-representation of foreign pupils in special education in the canton of Vaud: An analysis according to school type and region of origin - Bovey, Laurent; Bauer, Stéphanie; Bonvin, Patrick (Swiss Journal of Educational Research, 2022)
This article looks at the over-representation of foreign students in special education in the canton of Vaud. Based on a descriptive analysis of data from the Cantonal Research and Statistical Information Service of the canton of Vaud from 1996 to 2019, the article proposes to update the data on the subject and to verify whether this over-representation persists, and whether it manifests itself differently according to nationality or territorial grouping and according to the type of system to which the pupils are assigned (special classes or special schools).